2014
DOI: 10.1021/cb5007618
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Native Autoantigens via Antigen Surrogate Technology: Application to Type 1 Diabetes

Abstract: A fundamental goal in understanding the mechanisms of autoimmune disease is the characterization of autoantigens that are targeted by autoreactive antibodies and T cells. Unfortunately, the identification of autoantigens is a difficult problem. We have begun to explore a novel route to the discovery of autoantibody/autoantigen pairs that involves comparative screening of combinatorial libraries of unnatural, synthetic molecules for compounds that bind antibodies present at much higher levels in the serum of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…In an alternative approach very high density printed arrays of synthetic random peptide arrays were used for immunosignature discovery and were reported to exhibit higher accuracy than tiled peptide epitope arrays [37,38]. Since peptides may not be able to capture antibodies that bind to post-translational modifications and conformational epitopes Kodadek and coworkers pioneered the use of libraries of unnatural molecules and specifically peptoids (N-substituted oligoglycine polymers) for the discovery of surrogate antigen biomarkers from patient sera [29,39]. Other powerful methods that are currently used for antigen discovery include antigen microarrays [40,41], nucleic acid programmable protein arrays (NAPPAs) produced using in-vitro transcription/translation[42], peptide arrays [43] or finally arrays based on a different targets such as DNA, peptides and recombinant/native proteins [44].…”
Section: Antibody Serology: Future Directionsmentioning
confidence: 99%
“…In an alternative approach very high density printed arrays of synthetic random peptide arrays were used for immunosignature discovery and were reported to exhibit higher accuracy than tiled peptide epitope arrays [37,38]. Since peptides may not be able to capture antibodies that bind to post-translational modifications and conformational epitopes Kodadek and coworkers pioneered the use of libraries of unnatural molecules and specifically peptoids (N-substituted oligoglycine polymers) for the discovery of surrogate antigen biomarkers from patient sera [29,39]. Other powerful methods that are currently used for antigen discovery include antigen microarrays [40,41], nucleic acid programmable protein arrays (NAPPAs) produced using in-vitro transcription/translation[42], peptide arrays [43] or finally arrays based on a different targets such as DNA, peptides and recombinant/native proteins [44].…”
Section: Antibody Serology: Future Directionsmentioning
confidence: 99%
“…In a recent study, we identified GAD65 as a humoral autoantigen in the NOD mouse 10 and demonstrated that a GST-GAD65 fusion protein can be immobilized on glutathione-coated TentaGel beads without obstructing epitopes in GAD65 critical for autoantibody binding. We also have reported the isolation of a different antigen surrogate, compound 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, however, the immobilized antigen identifies an entirely different population of ATB patients; neither discovery nor test ATB patient sera that were positive for 2-B binding respond positively in the immobilized Ag85B ELISA. We have observed previously that antigen immobilization on an ELISA plate can occlude the epitope that the small-molecule is mimicking 14 . This does not rule out Ag85B as a diagnostic antigen or viable target for mimicry as a surrogate.…”
Section: Discussionmentioning
confidence: 99%